Developing High School Prep Class Students’ Verbal Skils by Using Web 2.0 Application - Gürbüz Ocak; Hateme Aysel Kuzu; Akın Karakuyu (e-Kafkas Eğitim Araştırmaları Dergisi)
With the importance of learning English and being able to communicate in the learned language, language education has become a considerable issue in all age groups. This important subject has become more difficult to implement with the Covid-19 pandemic. During the distance education which is applied in long period, students have experienced various problems in the lessons. In this study, it is tried to find the reasons, solutions and alternative ways of student’s unwillingness and hesitation of English speaking during their lessons. With the aim of finding these concerns an action research method, a qualitative research method, is used. 33 prep students from the high school in Bolvadin, Afyonkarahisar have attended to study. During and at the end of the applications, data were collected by teacher diaries, students diaries and semi-structured interview form. While the descriptive analysis method was used for the diaries, contents analysis was used for the interview form. At the end of the content analysis, it was found the codes and themes of focus group discussion data. As a result of data re-coding by the co-observer, the agreement was found to be 86 percent. When the applied action research data were anaylzed, it was determined that the students were embarrassed in the lessons and because of their speaking anxiety, they participated less in the activities. It has been concluded that the willingness to speak is increased with Web 2.0 applications and the lessons that include more dialogues, reading-listening activities, games and movies will be motivating for the students.